Platelet Phenotyping by Full Spectrum Flow Cytometry. Issue 2 (13th February 2023) - Spurgeon, Benjamin E. J.; Frelinger, Andrew L.
Abstract: Platelets play key roles in hemostasis, immunity, and inflammation, and tests of platelet phenotype and function are useful in studies of disease biology and pathology. Full spectrum flow cytometry offers distinct advantages over standard tests and enables the sensitive and simultaneous detection of many biomarkers. A typical assay provides a wealth of information on platelet biology and allows the assessment of in vivo activation and in vitro reactivity, as well as the discovery of novel phenotypes. Here, we describe the analysis of platelets by full spectrum flow cytometry and discuss a range of controls and methods for interpreting results. © 2023 Wiley Periodicals LLC. Basic Protocol : Platelet phenotyping by full spectrum flow cytometry Support Protocol 1 : Spectral unmixing Support Protocol 2 : Data preprocessing